Features of functioning of cetoniinae red and its derivatives in Ukrainian language (XI – XIII) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The study of the history of the vocabulary of the Ukrainian language is impossible without studying Stanovlenie separate semantic groups of vocabulary, in particular coloration. The article discusses the functioning of colorative red and its derivatives in Ukrainian language (XI – XIII). Fixed unlimited combinability nomen red, considered the use of tokens in the literal and figurative meanings.
Keywords: cetoniinae, token red; colorative; derived words; abstract words